The politics and policies of language use in African Union institutions - Tohouenou, Codjo Raymond (My University, 2018)
Upon its inception in May 1963, the founding fathers of the then Organization of African Unity (OAU), now African Union (or AU), demonstrated a great deal of commitment towards the achievement of what should be called - as far as this study is concerned - the ‘African linguistic dream’. In this dream, the OAU founding fathers saw an African citizen who is empowered linguistically (UNESCO, 2006).1 Consequently, they were determined to ensure the development and promotion of indigenous African languages. The Experts Meeting held in Harare, Zimbabwe, in March 1997, therefore acknowledged that - in Africa - language policies should be informed by an African dream (UNESCO, 2006: 50)2. There have been several initiatives, policies, programmes, etc., to promote and develop indigenous African languages some of which are the 1986 Language Plan of Action for Africa3, the creation of the OAU Inter-African Bureau of Languages (OAU-BIL) which was later replaced by the ACALAN (Matsinhe, 2013, 2015), and recently the AU’s Agenda 20634. However, more than half a century after independence, indigenous African languages have still not been accorded their rightful place in public life, media, education and national affairs. The African linguistic dream is yet to materialise. Paradoxically, these languages are recognised as national and even official languages. Such designations are pointless because they are not supported by clear policies capable of guiding their implementation. To this extent, there has been a big contradiction between these talks and the actual linguistic reality on the ground (Chimhundu, 2015). In this study, a qualitative approach was used to investigate why the implementation of the OAU/AU’s Language Plans of Action for Africa (LPAAs) has not led to an effective promotion of the language agenda. Qualitative methods such as purposive sampling, convenience sampling as well as snowball sampling strategies were used to gather views of language experts, language policy makers and implementers and politicians, and linguistic experts, some of whom have contributed to the drafting of the LPAAs. Twenty semi-structured individual interviews and two group interviews were conducted. Each of which was made up of 11 and 8participants, i.e., n=19, making a total of 39 participants. The interviews were all in English, and they were transcribed directly without being translated from or into any other language. A thematic analysis was then applied to the transcripts using the Framework Method. The study confirms that the implementation of the LPAAs has not contributed substantianly to the development and promotion of the effective use of indigenous African languages as there has been a significant shift from the OAU-BIL’s militant approach of eradication of the use of colonial languages, given the fact that it opposed the use of colonial languages from the onset in 1963, to a much softer stance since ACALAN - the Specialised Organ of the OAU/AU responsible for developing and promoting indigenous African languages - now calls for a partnership between African languages and colonial languages (African Union, 2015; Batibo 2015; Matsinhe, 2013: 27). Africa does not need to waste its precious time and resources on developing and promoting effective use of indigenous African languages because both LPAAs are still pertinent, topical and remain a reference (Chimhundu, 2015).
A thesis submitted to the University of the Witwatersrand in fulfillment of the requirements of the degree of Doctor of Philosophy in Translation and Interpreting Studies 2018
Keywords: Linguistics--South Africa; Language and languages